2021
DOI: 10.3390/plants10102049
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Using Paulownia elongata S. Y. Hu × Paulownia fortunei Hybrid for Phytoextraction of Toxic Elements from Post-Industrial Wastes with Biochar

Abstract: The potential of the Paulownia hybrid for the uptake and transport of 67 elements along with the physiological response of plants cultivated in highly contaminated post-industrial wastes (flotation tailings—FT, and mining sludge—MS) was investigated. Biochar (BR) was added to substrates to limit metal mobility and facilitate plant survival. Paulownia could effectively uptake and translocate B, Ca, K, P, Rb, Re and Ta. Despite severe growth retardation, chlorophyll biosynthesis was not depleted, while an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…have exceptional adaptive potential to survive under such extreme conditions, i.e., they do not require any specific habitat management for survival, and can play a significant role in the decontamination and amelioration of such habitats, especially during the initial stages of the revegetation process. [ 16 , 24 , 25 , 26 ]. In terms of FA, it has been shown that biological/technical reclamation and afforestation measures, combined with the spontaneous succession of plants, can contribute to the improvement of unfavorable physical and chemical characteristics of ash, including a reduction in the toxic concentrations of TEs in ash as the substrate on which plants grow, and may be advantageous for the development of dense and relatively species-rich vegetation on fly ash landfills and other disposal sites [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…have exceptional adaptive potential to survive under such extreme conditions, i.e., they do not require any specific habitat management for survival, and can play a significant role in the decontamination and amelioration of such habitats, especially during the initial stages of the revegetation process. [ 16 , 24 , 25 , 26 ]. In terms of FA, it has been shown that biological/technical reclamation and afforestation measures, combined with the spontaneous succession of plants, can contribute to the improvement of unfavorable physical and chemical characteristics of ash, including a reduction in the toxic concentrations of TEs in ash as the substrate on which plants grow, and may be advantageous for the development of dense and relatively species-rich vegetation on fly ash landfills and other disposal sites [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exclusively for salicylic acid determination, chromatographic analyses were performed with a Waters Alliance 2695 Chromatograph coupled with a Waters 2475 Multi-λ Fluorescence Detector (Waters Corporation, Milford, MA, USA), using a Waters Spherisorb ODS2 column (100 × 4.6 mm, 3 µm). The isocratic elution was performed with a 1.5 mL min −1 flow rate of potassium-acetate buffer (0.2 M, pH 5.0) [32]. The fluorometric detection was carried out at λ = 295 and 405 nm for excitation and emission, respectively.…”
Section: Profiling Of Phenolic Metabolites and Low-molecular-weight O...mentioning
confidence: 99%
“…Along with other tree Paulownia species can be used for phytoremediation purposes due to their tolerance to high concentrations of metals (Drzewiecka et al, 2021). In total, the sequential biorefinery of plant raw of Paulownia species allows using different plant parts for various purposes such as medicinal, biofuel, forage, etc.…”
Section: Introductionmentioning
confidence: 99%